Rater Reliability and Rater Effects of the Safe Driving Behavior Measure. - Classen, Sherrilene; Wen, Pey-Shan; Velozo, Craig A.; Bédard, Michel; Winter, Sandra M.; Brumback, Babette A.; Lanford, Desiree N. (American Journal of Occupational Therapy)
We used the Safe Driving Behavior Measure (SDBM) to determine rater reliability and rater effects (erratic responses, severity, leniency) in three rater groups: 80 older drivers (mean age = 73.26, standard deviation = 5.30), 80 family members or caregivers (age range = 20-85 yr), and two driving evaluators. Rater agreement was significant only between the evaluators and the family members or caregivers. Participants rated driving ability without erratic effects. We observed an overall rater effect only between the evaluator and family members or caregivers, with the evaluators being the more severe rater group. Training family members or caregivers to rate driving behaviors more consistently with the evaluator's ratings may enhance the SDBM's usability and provide a role for occupational therapists to interpret proxy reports as an entry point for logical and efficient driving safety interventions.